2010
DOI: 10.1590/s0103-84782010005000142
|View full text |Cite
|
Sign up to set email alerts
|

Estudo energético da produção de biocombustível a partir do milho

Abstract: RESUMO Objetivou-se analisar energeticamente a produção de etanol a partir do milho (Zea mays L.). As pesquisas de campo foram realizadas na região paulista do Médio ABSTRACT This research analyzed the energetic consumption of etanol from the corn crops (Zea mays L.). The field surveys were carried out in the Midle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 5 publications
0
8
0
3
Order By: Relevance
“…The cultural input of the system under high technological level was significantly higher than that observed in other systems (Table 1). According to SALLA et al (2010a), a conventional corn production has cultural inputs of 15,633.7MJ ha -1 higher than the value of the system discussed, due to the addition of transport in the technical itinerary. In a corn crop under direct seeding, MELO et al (2007), even including transport to the technical itinerary, found a lower value (11,270.23 and 13,771.95MJ ha -1 for two consecutive yields).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The cultural input of the system under high technological level was significantly higher than that observed in other systems (Table 1). According to SALLA et al (2010a), a conventional corn production has cultural inputs of 15,633.7MJ ha -1 higher than the value of the system discussed, due to the addition of transport in the technical itinerary. In a corn crop under direct seeding, MELO et al (2007), even including transport to the technical itinerary, found a lower value (11,270.23 and 13,771.95MJ ha -1 for two consecutive yields).…”
Section: Resultsmentioning
confidence: 98%
“…The application of non-renewable energy was lower than the application of biological energy (Table 3), representing 28.46% of total energy expenditure. According to SALLA et al (2010a), the adoption of alternative techniques of production, such as direct seeding, the use of renewable fuels in industrial and production systems, and the use of organic fertilizers can minimize the energy expenditure used in the production of corn. CAMPOS et al (2009) also highlights the need for new technological models that replace the use of fossil fuels, capable of providing to humans the comfort generated by mechanization and increased agricultural productivity and also the viability of sustainability in agriculture, by the use of renewable resources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Balanço energético no sistema misto de produção com integração lavoura-pecuária, rotação pasto/lavoura S3P e rotação lavoura/pasto S3L, com preparo convencional do solo (PC) e em sistema plantio direto (PD), entre 1991-2010, em experimento da Embrapa Cerrados, Planaltina, DF. (Salla et al, 2010). Em geral, os resultados de balanço energético obtidos no presente estudo foram favoráveis aos biocombustíveis produzidos em todos os sistemas, especialmente o bioetanol.…”
Section: Resultsunclassified
“…This is mainly because maize's energy use in Brazil is still not a significant reality (SALLA et al, 2010) as well as energy use analysis isusually not considered as often as management decisions.At world level, there is a greater quantity of such energy approach studies, especially because maize is the main source of ethanol in USA (GRASSINI; CASSMAN, 2012;MÉJEAN;HOPE, 2010;SHAPOURI, 2004).…”
Section: Introductionmentioning
confidence: 99%